합판 정재단 부산물을 중층 Core로 이용한 복합보드의 물리,기계적 성질에 관한 고찰 - 최송규; Song Kyu Choe; 피덕원; Duck Won Pi; 강석구; Seong Goo Kang (목재공학, 2013)
폐목재의 재활용으로 인한 보드의 물리·기계적 특성이 하락하는 경향이 있다. 그 원인으로는 가공되어 있던 재료를 재활용함에 있어 그 형상이 불균질하고 기존의 접착제 성분과 이물질로 인한 보드 품질의 불균일과 저하를 초래한다. 또한 접착제에 포함되어 있는 포름알데히드로 인해 높은 방산량을 가지게 된다. 이러한 제품의 질적 하락이 수입되는 파티클보드와의 가격 및 품질 경쟁력 약화로 이어져 국내 보드 산업의 문제점으로 대두되고있다. 따라서 본 연구에서는 최근 파티클보드의 원재료로 사용되고 있는 합판 정재단 부산물을 이용한 보드를 제조하고 각각의 제조 조건별 물리·기계적 특성을 평가하였다. 그 평가결과로 베니어 적층 복합보드를 EMDI 수지를 이용하여 4∼16 mesh의 일반적인 chip 크기로 중층을 제작했을 때 휨강도가 57.7 N/mm2로 OSB 측정결과 26.8 N/mm2에 비해 215% 높은 휨강도를 나타냈으며 7.1∼17.3%의 두께팽창률은 내수성을 지닌 보드로서 적합함을 보였다. 또한 0.7 ppm의 포름알데히드 방산량은 E1등급의 평균값 1.5 ppm과 E0 등급 최대값 0.7 ppm의 조건에 충족하며 이러한 결과는 바닥 깔개용 OSB를 대체가능할 것으로 사료된다. The board using recycled wood waste chip tends to decrease in terms of physical and mechanical properties. The reasons are notably different shape of chips, components of used adhesive and impurity content, which bring the irregular quality and downgrading of board. Moreover, the board has higher emissivity of formaldehyde than regular board, because recycled chip contains adhesives that were used to make previous products. Weakens the price and quality competiveness, and it led to bringing the issue of problem in Korean board industry. For these reason, in this study, boards using byproducts of plywood were made to evaluate physical and mechanical properties according to manufacturing conditions. As a result, The board was consists of 4~16 mesh chips for core layer and veneer on both face and they were combined using EMDI, and its` bending strength was 57.7 N/mm2 which is 215% higher than that of OSB(26.8 N/mm2). Moreover, the emissivity of formaldehyde was 0.7 ppm, this board seems to substitute OSB for rated sheathing.